Smart Energy Monitoring System using the ARAS Method (International Journal of Food and Nutritional Sciences, 2019)
Smart Energy Monitoring System Technology, of the plant Energy utilization of various areas24 Monitors around the clock. Energy Using the tracking system Accomplished by energymeters with data loggers. An IoT-Based Energy Monitoring System (EMS) Collect andorganize energy consumption information into meaningful and actionable insights offers, i.e.Energy Saving Opportunities (ECOs).